ANALISIS KINERJA PERANGKAT GAMPONG DALAM PENGEMBANGAN BUMG (Studi Kasus Pada Meunasah Kulam Meureudu Kabupaten Pidie Jaya) - Hasbi, Hasbi; Syahriani, Endang; Ferdiananda Chadafi, Muhammad; Haryani, Haryani (Fakultas Ekonomi Universitas Almuslim Bireuen, 2025)
The study analyzed the performance of the device in the development of BUMG by reviewing the influence of the keuchik leadership factor and increasing sources of income. The study was conducted at BUMG Meunasah Kulam, Meureudu District, Pidie Jaya Regency. The type of quantitative research with causality analysis. The data analysis technique used was path analysis using SMART-PLS. The results obtained (1) BUMG development is influenced by keuchik leadership and the contribution of income source factors also influences BUMG development, (2) Gampong device performance and also increasing sources of income have a significant effect on BUMG development. (3) Keuchik leadership has a significant effect on Gampong device performance. (4) The influence of Leadership, Increasing Sources of Income, and Gampong Device Performance simultaneously on the Development of Village-Owned Enterprises by 76.1%. (5) Leadership and Increasing Sources of Income affect Gampong Device Performance by 77.9%.